Leucophyllum frutescens mediated synthesis of silver and gold nanoparticles for catalytic dye degradation - Gami, Bansuri; Bloch, Khalida; Mohammed, Shahansha M.; Karmakar, Srikanta; Shukla, Satyajit; Asok, Adersh; Thongmee, Sirikanjana; Ghosh, Sougata (Frontiers in Chemistry, 2022)
In recent years, the excessive use of synthetic organic dyes in textiles, tannery, cosmetics and food industries has posed a severe threat to the environment. Hence, the application of nanotechnology is gaining worldwide attention due to attractive physico-chemical and opto-electronic properties of nanoparticles that can be also employed for catalytic dye degradation.This study reports a phytogenic approach for fabrication of silver (AgNPs) and gold nanoparticles (AuNPs) using Leucophyllum frutescens leaf extract (LFLE). The AgNPs were spherical, whereas anisotropic AuNPs were spherical, triangular and blunt ended hexagons. The majority of the spherical AgNPs and AuNPs were 50±15 nm and 22±20 nm, respectively. Maximum synthesis of AgNPs was obtained when 5mM for AgNO3 reacted with 10% LFLE for 48 h at 50 °C. Likewise, AuNPs synthesis was highest when 2mM HAuCl4 reacted with 10% LFLE for 5 h at 30 °C. The average hydrodynamic particles size of AgNPs was 34.8 nm while AuNPs was 140.8 nm as revealed using dynamic light scattering (DLS) that might be due to agglomeration of smaller nanoparticles into larger clusters. ZETA potential of AgNPs and AuNPs were 0.67mV and 5.70 mV, respectively. X-ray diffraction (XRD) analysis confirmed the crystallinity of the nanoparticles. Fourier transmission infrared spectroscopy (FTIR) confirmed that various functional groups from the phytochemicals present in LFLE played a significant role in reduction and stabilization during the biogenic synthesis of the nanoparticles. The bioreduced AgNPs and AuNPs catalytically degraded Rhodamine B dye (RhB) in presence of UV-light with degradation rate constants of 0.0231 s-1 and 0.00831 s-1, respectively. RhB degradation followed a first order rate kinetics with 23.1 % and 31.7 % degradation by AgNPs and AuNPs, respectively.